Detection of antibiotic residues in cow’s milk using microbiological screening test in Souk Ahras, Algeria - Batah, R; Belbel, Z; Melouah, K; Labied, I; Benaldjia, L; Berreghis, A (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of the present study was to investigate antibiotic residues in raw and fermented cow’s milk in Souk Ahras region, Algeria. A total of 78 cow’s milk samples were collected, including 46 samples of raw milk from various farms and 32 samples of fermented cow’s milk purchased from various points of sale. Samples were examined using a microbiological test (the European four-plate test). Results indicate that only 35 (17/46 raw milk and 18/32 fermented milk) samples were free from antibiotic residues. A high prevalence of antibiotic residues was observed in both raw and fermented milk (63,04%) and (43,75%), respectively. β-lactams and/or tetracyclines were the most detected in both raw and fermented milk, with (47,83%) and (43,75%), respectively. A rate of 30.43% for aminoglycosides, 15.22% for β-lactams and/or macrolides, and 13.04% for sulfonamides were detected in raw cow’s milk. However, a rate of 18.75% for macrolides and/or β-lactams, 12,50% for aminoglycosides, and 3.12% for sulfonamides were detected in fermented milk. A rate of 62.07% of raw milk was contaminated with one family of antibiotics. Werehase (64.28%) of fermented milk was positive for two families of antibiotics. This preliminary study allowed us to outline the presence of antibiotic residues in raw and fermented cow’s milk in Souk-Ahras region. Failure to adhere to good antibiotic usage practices, particularly regarding the withdrawal periods after treatment, can lead to the presence of residues in animal products, thereby exposing consumers to health risks. Keywords: Antibiotic residues; Bacillus subtilis; Fermented milk; Four plate test; Micrococcus luteus; Raw milk. REFERENCES Alimohammadi, M., Askari, S. G., Azghadi, N. M., Taghavimanesh, V., Mohammadimoghadam, T., Bidkhori, M., Gholizade, A., Rezvani, R., & Mohammadi, A. A. (2020) Antibiotic residues in the raw and pasteurized milk produced in Northeastern Iran examined by the four-plate test (FPT) method. International Journal of Food Properties, 23(1), 1248‑1255. https://doi.org/10.1080/10942912.2020.1800032 Alnassrallah, M. N., Alzoman, N. Z., & Almomen, A. (2022) Qualitative immunoassay for the determination of tetracycline antibiotic residues in milk samples followed by a quantitative improved HPLC-DAD method. Scientific Reports, 12(1), 14502. https://doi.org/10.1038/s41598-022-18886-2 Baazize-Ammi, D., Dechicha, A. S., Tassist, A., Gharbi, I., Hezil, N., Kebbal, S., Morsli, W., Beldjoudi, S., Saadaoui, M. R., & Guetarni, D. (2019) Screening and quantification of antibiotic residues in broiler chicken meat and milk in the central region of Algeria. Revue Scientifique Et Technique (International Office of Epizootics), 38(3), 863‑877. https://doi.org/10.20506/rst.38.3.3031 Bacanlı, M., & Başaran, N. (2019) Importance of antibiotic residues in animal food. Food and Chemical Toxicology, 125, 462‑466. https://doi.org/10.1016/j.fct.2019.01.033 Butovskaya, E., Gambi, L., Giovanetti, A., & Fedrizzi, G. (2023) Screening of antibiotic residues in raw bovine milk in Lombardy, Italy : Microbial growth inhibition assay and LC-HRMS technique integration for an accurate monitoring. Heliyon, 9(4), e15395. https://doi.org/10.1016/j.heliyon.2023.e15395 Chen, J., Ying, G.-G., & Deng, W.-J. (2019) Antibiotic Residues in Food : Extraction, Analysis, and Human Health Concerns. Journal of Agricultural and Food Chemistry, 67(27), 7569‑7586. https://doi.org/10.1021/acs.jafc.9b01334 Layada, S., Benouareth, D.-E., Coucke, W., & Andjelkovic, M. (2016) Assessment of antibiotic residues in commercial and farm milk collected in the region of Guelma (Algeria). International Journal of Food Contamination, 3(1), 19. https://doi.org/10.1186/s40550-016-0042-6 Liu, Y., Luo, Y., Li, W., Xu, X., Wang, B., Xu, X., Hussain, D., & Chen, D. (2024) Current analytical strategies for the determination of quinolone residues in milk. Food Chemistry, 430, 137072. https://doi.org/10.1016/j.foodchem.2023.137072 Meklati, F. R., Panara, A., Hadef, A., Meribai, A., Ben-Mahdi, M. H., Dasenaki, M. E., & Thomaidis, N. S. (2022) Comparative Assessment of Antibiotic Residues Using Liquid Chromatography Coupled with Tandem Mass Spectrometry (LC-MS/MS) and a Rapid Screening Test in Raw Milk Collected from the North-Central Algerian Dairies. Toxics, 10(1), 19. https://doi.org/10.3390/toxics10010019 Merhi, A., Khatib, S. E., Haddad, J., & Hassan, H. F. (2023) A review of the antibiotic residues in food in the Arab countries. Applied Food Research, 3(2), 100332. https://doi.org/10.1016/j.afres.2023.100332 Mouliom Mouiche, M. M., Okah-Nnane, N. H., Moffo, F., Djibo, I., Mapiefou, N. P., Mpouam, S. E., Mfopit, Y. M., Mingoas, J.-P. K., Tebug, S. F., & Ndukum, J. A. (2024) Antibiotic Residues in Foods of Animal Origin in Cameroon : Prevalence, Consumers’ Risk Perceptions, and attitudes. Journal of Food Protection, 87(4), 100237. https://doi.org/10.1016/j.jfp.2024.100237 Niu, C., Yan, M., Yao, Z., & Dou, J. (2023) Antibiotic residues in milk and dairy products in China : Occurrence and human health concerns. Environmental Science and Pollution Research International, 30(53), 113138‑113150. https://doi.org/10.1007/s11356-023-30312-2 Onyinye Stella, O.-I., Vivienne Ezenduka, E., & John Anaelom, N. (2020) Screening for tylosin and other antimicrobial residues in fresh and fermented (nono) cow milk in Delta state, South-South, Nigeria. Veterinary World, 13(3), 458‑464. https://doi.org/10.14202/vetworld.2020.458-464 Ouabdesselam, L., Benmaamar, Z., & Berbar, A. (2020) Contribution to the Identification of Antibiotics Residues in Raw Bovine Milk in Algeria. European Journal of Basic Medical Sciences, 10(1), 43‑46. https://doi.org/10.21601/ejbms/9314 Parmar, J. K., Chaubey, K. K., Gupta, V., & Bharath, M. N. (2021) Assessment of various veterinary drug residues in animal originated food products. Veterinary World, 14(6), 1650‑1664. https://doi.org/10.14202/vetworld.2021.1650-1664 Sachi, S., Ferdous, J., Sikder, M. H., & Azizul Karim Hussani, S. M. (2019) Antibiotic residues in milk : Past, present, and future. Journal of Advanced Veterinary and Animal Research, 6(3), 315‑332. https://doi.org/10.5455/javar.2019.f350 Titouche, Y., Akkou, M., & Houali, K. (2022) Detection of antimicrobial residues in bovine meat marketed at Tizi-Ouzou area (Algeria), by a microbial screening assay. Journal of the Hellenic Veterinary Medical Society, 73(2), Article 2. https://doi.org/10.12681/jhvms.26396 Treiber, F. M., & Beranek-Knauer, H. (2021) Antimicrobial Residues in Food from Animal Origin-A Review of the Literature Focusing on Products Collected in Stores and Markets Worldwide. Antibiotics (Basel, Switzerland), 10(5), 534. https://doi.org/10.3390/antibiotics10050534 Wu, Q., Shabbir, M. A. B., Peng, D., Yuan, Z., & Wang, Y. (2021) Microbiological inhibition-based method for screening and identifying of antibiotic residues in milk, chicken egg and honey. Food Chemistry, 363, 130074. https://doi.org/10.1016/j.foodchem.2021.130074 Yamada, Y., Sasaki, J., Matsuzaki, T., & Shiiki, K. (1981) Influence of medium and diluent pH and diffusion time on antibiotic bioassay. The Tokai Journal of Experimental and Clinical Medicine, 6(1), 23‑33. Yazdanpanah, H., Osouli, M., Salamzadeh, J., Rashidi, E., Karimi, Z., Beykmohammadi, L., & Eslamizad, S. (2023) Simultaneous Screening of Six Families of Antibiotic Residues in Milk Samples by Biochip Multi-array Technology. Iranian Journal of Pharmaceutical Research: IJPR, 22(1), e136363. https://doi.org/10.5812/ijpr-136363 Zeghilet, N., Bouchoucha, B., & Bouaziz, O. (2022) βeta-lactam and Tetracycline Antibiotic Residues in Cow Milk in the Constantine region, Algeria. | Veterinarska Stanica | EBSCOhost. https://doi.org/10.46419/vs.53.3.8